An Overview of the Impact of the Food Sector “Intelligent Packaging” and “Smart Packaging” - Maria POLI; Konstantinos MALAGAS; Spyridon NOMIKOS; Apostolos PAPAPOSTOLOU; Grigoris VLASSAS (European Journal of Interdisciplinary Studies)
The contribution of traditional packaging was significant to the initial development of food distribution systems; however, it can no longer meet the growing demands of modern consumers, businesses, and the rapidly evolving supply chain. New advances in various sciences, particularly in information and communication technologies (ICT), contribute to the emergence of new forms of packaging. The transition to “innovative packaging” with additional functions is beneficial for all participants in the food chain. “Intelligent packaging” and “smart packaging” both provide helpful information and continuous monitoring of the food / product safety and quality during the whole chain. Packaging should be seen as an entire system and offers many benefits to many sectors of our society, such as economic rewards, reduction of food waste, increased food safety, contribution to the circular economy, and in general, responds better to the growing demands of users in their daily lives. The current research reviewed a large number of relevant studies, discussed the main issues, and finally, functional outcomes were generated. Practitioners and academicians will benefit from the current study and acquire helpful knowledge on an exciting topic.